The Effect of Centralistic Political Party Policies in Selection Of Regional Heads in Medan City - Benito Asdhie Kodiyat MS; Abdul Hakim Siagian; Andryan Andryan (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
The problem of the realization of regional autonomy-decentralization will be successfully achieved if in the process of determining regional leaders are still in the shadow of the national political elite. More broadly, this does not provide an opportunity for the people of the region to freely determine their future leaders in the area. To a certain degree, this kind of process will destroy regional democratization. For that reason, the problem to be examined is how the influence of the centralization of political party policy in relation to the election and determination of regional head candidates carried by political parties, we need to discuss in advance what is the cause of the direct implementation of regional head elections and how the role of political parties in recruiting regional head candidates. The research method used is normative legal research. The results showed that the election of regional heads that had experienced a shift from indirect elections in the DPRD to direct elections by the people had constructive consequences for democracy and the conception of popular sovereignty in the context of elections and the role of political parties that were very strategic in being able to carry prospective candidates for heads regions become candidates for regional heads in the regional head election experiencing conceptual ambivalence.